Planetesimals around stars with TESS (PAST) – I. Transient dimming of a binary solar analogue at the end of the planet accretion era. Issue 4 (12th July 2019) - Gaidos, E; Jacobs, T; LaCourse, D; Vanderburg, A; Rappaport, S; Berger, T; Pearce, L; Mann, A W; Weiss, L; Fulton, B; Behmard, A; Howard, A W; et al.
ABSTRACT: We report detection of quasi-periodic (1.5-d) dimming of HD 240779, the solar-mass primary in a 5 arcsec visual binary (also TIC 284730577), by the Transiting Exoplanet Survey Satellite . This dimming, as has been shown for other 'dipper' stars, is likely due to occultation by circumstellar dust. The barycentric space motion, lithium abundance, rotation, and chromospheric emission of the stars in this system point to an age of ≈125 Myr, and possible membership in the AB Doradus moving group. As such it occupies an important but poorly explored intermediate regime of stars with transient dimming between young stellar objects in star-forming regions and main-sequence stars, and between UX Orionis-type Ae/Be stars and M-type 'dippers'. HD 240779, but not its companion BD+10 714B, has Wide-field Infrared Survey Explorer (WISE) -detected excess infrared emission at 12 and 22 μ m indicative of circumstellar dust. We propose that infrared emission is produced by collisions of planetesimals during clearing of a residual disc at the end of rocky planet formation, and that quasi-periodic dimming is produced by the rapid disintegration of a ≳100 km planetesimal near the silicate evaporation radius. Further studies of this and similar systems will illuminate a poorly understood final phase of rocky planet formation like that which produced the inner Solar system.